Binuclear coordination complex of open merocyanine form of photochromic spiropyran with MnII(hfac)2 having high spin (S = 5) ground state. (28th February 2023) - Osipov, Nikita G.; Faraonov, Maxim A.; Shestakov, Alexander F.; Mikhailenko, Maxim V.; Kuzmin, Alexey V.; Khasanov, Salavat S.; Otsuka, Akihiro; Yamochi, Hideki; Kitagawa, Hiroshi; Konarev, Dmitri V.
Abstract : The interaction of 1, 3, 3-trimethylindolino-β-naphthopyrylospiran (TMI-NPS) with manganese(ii ) hexafluoroacetylacetonate yields crystals of {Mn II (hfac)2 ( μ 2 -TMI-NPS)}2 (1 ) in which Mn(ii ) atoms are bridged by oxygen atoms of ring-opened TMS-BPI into the dimer. Abstract : Photochromic molecules can transform from colorless closed to colored open forms by coordination with metal ions. Interaction of photochromic 1, 3, 3-trimethylindolino-β-naphthopyrylospiran (TMI-NPS) with manganese(ii ) hexafluoroacetylacetonate in o -dichlorobenzene results in the formation of deep red-violet solution indicating a coordination-induced transition from closed to colored open form. Precipitation of crystals yields {Mn II (hfac)2 ·( μ 2 -TMI-NPS)}2 dimers (1 ) in which two Mn(ii ) atoms of hexafluoroacetylacetonate are bridged by oxygen atoms of two TMI-NPS ligands in the open form. Magnetic studies show a weak ferromagnetic exchange between Mn II spins through oxygen atoms of TMI-NPS with estimated exchange interaction ( J ) of +1.07 cm −1 . A positive Weiss temperature of +8 K also supports ferromagnetic coupling. As a result, Mn II spins arrange parallel to each other at 2 K, and correspondingly, these dimers transfer to a high spin ( S = 5) state. DFT calculations support noticeable mixing of the metal and ligand orbitals and essential positive charge on the TMI-NPS ligands, which can provide ferromagnetic exchange between Mn II spins.